A population-based and symptom-based COVID-19 prevalence survey - Reza Beiranvand; Maryam Azimzadeh; Maryam Chegeni; Shahnaz Ghalavandi; Zahra Mohseni; Ehteram Yousefi; Zaher Khazaei; Yasan Kazemzadeh; Kaivan Gheysvandi; Elham Gheysvandi (Wolters Kluwer Medknow Publications, 2023)
The current study aimed to determine the community-based COVID-19 prevalence and compare the symptom-based and test-based prevalence rates in the Omicron peak (February 20 to March 20, 2022) to assess community involvement and provide effective healthcare. This cross-sectional and population-based study examined the prevalence of COVID-19 from February 20 to March 20, 2022, in the city of Khomein in Markazi Province (located in central Iran) through random cluster sampling. The period prevalence of recurrent Omicron symptoms was 37.69%. Factors such as residence in urban areas (OR = 1.25, 95% CI: 0.95-1.66), number of COVID-19 vaccine doses (OR = 0.80, 95% CI: 0.67-0.95), the interval of last vaccination dose (OR = 1.04, 95% CI: 0.97-1.11) and a history of COVID-19 (OR =1.20, 95% CI: 1.04-1.39) were among the most important risk factors for Omicron. Ongoing efforts to vaccinate high-risk populations as well as stronger actions to diminish the Omicron consequences are fundamental obligations of the health system.